A tetrameric perylene diimide non-fullerene acceptor via unprecedented direct (hetero)arylation cross-coupling reactions. Issue 81 (25th September 2018) - Payne, Abby-Jo; Song, Jiali; Sun, Yanming; Welch, Gregory C.
Abstract : This study reports on the synthesis of an indancenodithiophene perylene diimide tetramer via unique direct (hetero)arylation reactivity. Abstract : This study reports on the synthesis of an indancenodithiophene perylene diimide tetramer via unique direct (hetero)arylation reactivity. The thiophene based core structure is shown to be easily functionalized with four perylene diimides at the four active C–H positions. This new reactivity provides a simple synthetic pathway towards tetrameric perylene diimides which have emerged as one of the best classes of electron acceptors for organic solar cells.